КОМПЬЮТЕРНЫЕ ИГРЫ В ОБУЧЕНИИ ИНОСТРАННОМУ ЯЗЫКУ - Jabborova, Shoira (Журнал иностранных языков и лингвистики, 2021)
The article outlines the usage of modern information technologies, namely computer games in teaching a foreign language. Problems of the use of computer games at lessons are touched upon. The article reviews the most popular computer games in the field of foreign languages.